Dr. Ernesto Galarza Scholarship Symposium Program 2007 - Chicano/Latino Faculty and Staff Association::::::::::::::: (2024)
Program for the 22nd Annual Dr. Ernesto Galarza Scholarship Symposium, held at San Jose State University on Thursday, May 10, 2007 at 5:30 PM – 8:00 PM in the Dr. Martin Luther King, Jr. Library. The event included a Registration/Reception, Welcome/Opening Remarks by Dr. Henry Gutierrez (President, CLFSA), Presentation of Scholarships by the Dr. Ernesto Galarza Scholarship Committee (Peggy Cabrera – Chair, Dr. Dolores DeHaro Mena – Committee Member, Elizabeth Munoz-Rosas, Committee Member), Keynote Address by Ana Lilia Soto (Dr. Ernesto Galarza Scholar), and Closing Remarks by Dr. Henry Gutierrez. Twelves awards were presented: Dr. Ernesto Galarza Scholarship, Cesar E. Chavez Memorial Scholarship, Chicano/Latino Faculty and Staff Association Scholarship (2 awards), National Association for Chicana and Chicano Studies Scholarship, Castellano Family Foundation Scholarship (5 awards), Simona-Beatriz Memorial Scholarship, and Marisol Perez Memorial Scholarship.